Spirit of truth: the Holy Spirit in Johannine tradition / 1 The origins of Johannine pneumatalogy - Breck, John (Spirit of truth the Holy Spirit in Johannine tradition, 1991)
pt. I The Spirit in the Old Testament and ancient near-east : The Spirit in Israel's salvation history -- The Spirit and the word in Hebrew prophecy -- The Spirit-concept in the ancient near-east -- pt. II The Spirit in the Hellenistic age : Jewish wisdom tradition -- Hellenistic sources -- The Dead Sea scrolls.